Desarrollo de una aplicación web y móvil para la gestión de pedidos de la empresa embutidos “San José”. - Quinga Araujo, Julio Cesar (2021)
Today the use of smart devices entails the use of mobile applications which aim to meet the needs of users in different fields such as entertainment, education, work, commerce, etc. Technological advances and the evolution of technological industries allow for a wide range of mobile devices that allow greater accessibility to new applications reaching more users, many companies dedicated to commerce and that use web and mobile applications to promote and market their products have had a better participation in the market, so the implementation of this web and mobile application for orders for the sausage trade will have a good acceptance by the "San José" Factory, considering that it is intended to streamline and manage better processes. as well as receiving new customers. In addition, with this new project, the Factory will generate new promotion and sales strategies for its products, standing out from other companies such as ice cream, dairy, sausage production factories, etc. Which belong to the Salcedo canton, renewing with new technologies, increasing its popularity inside and outside the province. Through the implementation of this application, there will be very important improvements in the processes of receiving and delivering orders, providing the client and administrator with intuitive applications that will facilitate the processes to be fulfilled, the client will be able to place their orders easily through the App and the administrator can manage the delivery. . Above all, this application will seek to ensure that customers get a good impression of the service offered by the factory and that in the near future they will return and thus be able to consolidate a fixed clientele.